Recruitment of Irgb6 to the membrane is a direct trigger for membrane deformation - Yamada, Hiroshi; Abe, Tadashi; Nagaoka, Hikaru; Takashima, Eizo; Nitta, Ryo; Yamamoto, Masahiro; Takei, Kohji (Frontiers in Cellular and Infection Microbiology, 2022)
Irgb6 is a member of interferon gamma-induced immunity related GTPase (IRG), and one of twenty “effector” IRGs, which coordinately attack parasitophorous vacuole membrane (PVM), causing death of intracellular pathogen. Although Irgb6 plays a pivotal role as a pioneer in the process of PVM disruption, the direct effect of Irgb6 on membrane remained to be elucidated. Here, we utilized artificial lipid membranes to reconstitute Irgb6-membrane interaction in vitro, and revealed that Irgb6 directly deformed membrane. Liposomes incubated with recombinant Irgb6 were drastically deformed generating massive tubular protrusions in the absence of guanine nucleotide, or with GMP-PNP. Liposome deformation was abolished by incubating with Irgb6-K275A/R371A, point mutations at membrane targeting residues. The membrane tubules generated by Irgb6 were mostly disappeared by the addition of GTP or GDP, which are caused by detachment of Irgb6 from membrane. Binding of Irgb6 to the membrane, which was reconstituted in vitro using lipid monolayer and quantified, revealed that the binding of Irgb6 was stimulated at GTP-bound state. Irgb6 GTPase activity was stimulated by the presence of liposomes more than eightfold. Irgb6 GTPase activity was also stimulated, although less efficiently, by lowering ionic strength, or by increasing protein concentration, indicating synergistic stimulation of the GTPase activity. These results suggest that membrane targeting Irgb6 and resulting deformation does not require GTP, but converting into GTP-bound state is crucial for detaching Irgb6 from the membrane, which might coincident with local membrane disruption.